2007
DOI: 10.1101/lm.425907
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7)-induced plasticity changes in the lateral amygdala are mediated by COX-2 and NO

Abstract: It is known from studies outside the brain that upon binding to its receptor, angiotensin-(1-7) elicits the release of prostanoids and nitric oxide (NO). Cyclooxygenase (COX) is a key enzyme that converts arachidonic acid to prostaglandins. Since there are no data available so far on the role of COX-2 in the amygdala, in a first step we demonstrated that the selective COX-2 inhibitor NS-398 significantly reduced the probability of long-term potentiation (LTP) induction in the lateral nucleus of the amygdala. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 46 publications
(59 reference statements)
2
19
0
Order By: Relevance
“…As described previously in male mice [14], the pretreatment of slices with Ang-(1–7) significantly enhanced LA-LTP (males: 173.3 ± 8.8%, n = 6 slices; p < 0.05). The same enhancement was also observed in slices derived from female wt mice (females: 173.3 ± 4.8%, n = 9 slices; p < 0.05; fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…As described previously in male mice [14], the pretreatment of slices with Ang-(1–7) significantly enhanced LA-LTP (males: 173.3 ± 8.8%, n = 6 slices; p < 0.05). The same enhancement was also observed in slices derived from female wt mice (females: 173.3 ± 4.8%, n = 9 slices; p < 0.05; fig.…”
Section: Resultssupporting
confidence: 74%
“…Angiotensin-(1–7) (Ang-(1–7)) is an endogenous peptide in the brain RAS with several beneficial effects that are often the opposite of those attributed to angiotensin II (Ang II) [10,11,12]. Recently, we showed that Ang-(1–7) increases long-term potentiation (LTP) not only in the CA1 region of the hippocampus [13], but also in the lateral nucleus of the amygdala (LA) [14], which is in contrast to the LTP suppression mediated by Ang II [15]. A G-protein-coupled receptor, Mas, encoded by the Mas proto-oncogene, has been identified as a possible receptor for Ang-(1–7) [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, Mas may not only lead to the release of nitric oxide by interacting with AT1 receptors but also be capable of directly acting on nitric oxide (NO) formation (Gwathmey et al 2010). Within the amygdala, Ang-(1-7) is capable of increasing LTP and data hint that this effect is mediated by nitric oxide, since blockage of NO-synthesis with L-NAME resulted in a blockage of the Ang-(1-7)-mediated increase in LTP (Albrecht 2007). Within the hippocampus, strong Mas immunoreactivity has been detected in the DG.…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting findings are probably due to differences in the models used and to cell-specific Ang-(1-7) signaling in the kidney, for example the dependency of each model on COX-2-mediated events, which can be differentially modulated by Ang-(1-7) (Albrecht 2007, Menon et al 2007, and highlight the need for further in vivo studies related to the RAS and its novel axis in kidney disease.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%